Nursing care in the prevention of pressure injury in prone COVID-19 patients: an integrative literature review (Research, Society and Development, 2022)
The objective was to determine the nursing care for the prevention of pressure injury in a patient with COVID-19 in the prone position. The method used was to perform an analysis of selected articles in the Virtual Health Library database, using the descriptors: COVID-19 AND pressure ulcer, critical care AND pressure injury AND COVID-19, pressure injury AND prevention AND COVID-19, nursing AND prone position, as exclusion criteria, titles and abstracts were read, after which they were grouped in order to respond to the objective. Of the selected articles, these were separated on the pathophysiology of pressure injuries, the sites conducive to pressure injuries in pronation, prevention measures and risk assessment, making it possible to identify nursing care for the prevention of pressure injuries that cover actions before and after the maneuver, and also in specific injuries considered unavoidable where their aggravation must be avoided. It is concluded that the patient affected by COVID-19 has specificities and requires prevention measures based and analyzed in scientific studies, to standardize them accurately and effectively in the clinical practice of health professionals.